Diversity and Distribution Pattern of Tree Species in Niyamgiri Hill Ranges, Orissa, India - Dash, P. K.; Mohapatra, P. P.; Giri Rao, Y. (Indian Forester, 2009)
The Niyamgiri hills in the South-Eastern parts of Orissa are a unique forest ecosystem harbouring rich floristic composition and vast natural resources. As there is absolutely no published record on flora of the hill till date, the phytosociological characteristics, diversity and distribution of tree species at three proposed reserve forests of the hill ranges between elevations from 400-1,306 m were studied. A total of 152 tree species were recorded from the study sites belonging to 114 genera and 41 families. Species diversity was found to be maximum at Khambesi Reserve Forest and minimum at Niyamgiri Reserve Forest. Significant correlation of species diversity with species evenness and species richness were observed while significant negative correlations were marked between species diversity, concentration of dominance, beta diversity and maturity index. At present the biodiversity of the hill is under threat due to the ongoing and upcoming mining activities. The results of this study might render a helping hand to the forest managers in preparing a conservation plan for the highly species diverse and threatened ecosystem of the hill ranges.